EVALUATION OF CORPORATE SOCIAL RESPONSIBILITY PROGRAM IMPLEMENTATION IN BOGOR PDAM TIRTA PAKUAN, WEST JAVA PROVINCE - Ismartaya Ismartaya; Djaali Djaali; suparno Eko Widodo (IJHCM (International Journal of Human Capital Management), 2017)
The purpose of this research is to determined whether the evaluation corporate social responsibility program implementation in Bogor PDAM Tirta Pakuan has been implemented in accordance with the vision, mission, and objectives of the company. PDAM Tirta Pakuan has a vision of CSR as a pioneer in the implementation of social responsibility in Bogor city especially and Indonesia in generally. Through this vision, PDAM Tirta Pakuan Bogor city, would really seriously on the implementation of the CSR programs. Based on these purposes, this research is done by evaluating the CSR programs which implemented by PDAM Tirta Pakuan Bogor city and use CIPP evaluation model to conduct an evaluation of the program. The type which used on this research is evaluation research with use qualitative approach. The source of information used is the Chief Executive of CSR PDAM Tirta Pakuan Bogor. Data collected by the observation, interview and documentation. Test validity of this research by using triangulation technique, while data analysis is done by reducing the data, presenting and concluding . The result shows that the program Tirta Pakuan care as the company’s strategy goes according to the purposes and plans that have been made by the company.Keywords: evaluation, corporate social responsibility, CIPP Model